Формування і розвиток лідерських якостей у студентів психологів під час навчання - Романовський, Олександр Георгійович; Петрова, А. В. (НТУ "ХПІ", 2016)
Формування лідерських якостей – це процес і результат розвитку внутрішньої структури, тобто психологічної організації особистості в єдності їх прояву з персональною організаторською та комунікативною готовністю до зовнішнього керівництва. Підготовка психологів-лідерів в умовах ВНЗ спрямована на підвищення рівня їх не тільки професійної, але й соціальної компетентності, розвиток лідерських рис фахівця. Лідерські якості студентів психологів змінюються під час навчання у вузі під впливом певних обставин та індивідуальних особливостей.

Formation of leadership qualities – it is a process and result of the development of the internal structure, that is, psychological organization of personality in the unity of their displays with personalized communication and organizational readiness for external management. Preparing leaders psychologists in the conditions of high school is aimed at increasing the level of not only professional, but also social skills, developing leadership qualities of the expert. Leadership students psychologists vary during training in high school under the influence of certain circumstances and individual characteristics.
Formation and leadership development in psychylogy students during training
Keywords: фахівець; комунікативні здібності; організаторські здібності; ВНЗ; керівництво; professional; communication skills; organizational skills